2014
DOI: 10.1007/s00285-014-0814-7
|View full text |Cite
|
Sign up to set email alerts
|

Global dynamics of the buffered chemostat for a general class of response functions

Abstract: We study how a particular spatial structure with a buffer impacts the number of equilibria and their stability in the chemostat model. We show that the occurrence of a buffer can allow a species to persist or on the opposite to go extinct, depending on the characteristics of the buffer. For non-monotonic response functions, we characterize the buffered configurations that make the chemostat dynamics globally asymptotically stable, while this is not possible with single, serial or parallel vessels of the same t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…The performance is considered for different criteria studied in the literature [31], among which the most common are: the output substrate concentration, the residence time, the biogas flow rate and the biomass productivity. Particular interconnection structures have been investigated and compared for the properties in terms of input-output performances (see for instance [5,7,15,28]). It has been notably shown that a series of reactors instead of a single perfectly mixed one can significantly improve the performances of the bioprocess (in terms of matter conversion) while preserving the same residence time, or equivalently that the same performance can be obtained with a smaller residence time considering several tanks in series instead of a single one [14,17,24,25,47].…”
Section: Introductionmentioning
confidence: 99%
“…The performance is considered for different criteria studied in the literature [31], among which the most common are: the output substrate concentration, the residence time, the biogas flow rate and the biomass productivity. Particular interconnection structures have been investigated and compared for the properties in terms of input-output performances (see for instance [5,7,15,28]). It has been notably shown that a series of reactors instead of a single perfectly mixed one can significantly improve the performances of the bioprocess (in terms of matter conversion) while preserving the same residence time, or equivalently that the same performance can be obtained with a smaller residence time considering several tanks in series instead of a single one [14,17,24,25,47].…”
Section: Introductionmentioning
confidence: 99%
“…For such cases, there is a unique positive equilibrium in the first tank as well. In [37], the following result is given.…”
mentioning
confidence: 99%
“…It has been shown in [37] that the graphs of the family of functions φ r (·) for r ∈ (0, 1) have the point (s 1 , D) in common, wheres 1 = αs 2 + (1 − α)S in . there always exist functions φ r (·) whose graph possesses a unique intersection with the graph of µ(·).…”
mentioning
confidence: 99%
See 2 more Smart Citations